The control of synthetic cannabinoids potentiates the toxicity of emerging substances. (29th March 2019) - Couceiro, Joana; Quintas, Alexandre
Abstract : Introduction: Novel psychoactive substances (NPS) is becoming a major public health concern as their use grows. In the EU, synthetic cannabinoids (SC) are the most frequently reported class of NPS. SC are widely distributed as 'legal' substitutes of cannabis. However, these substances are just legal until scheduled by specific legislation [1 ]. Following identification of the first SC, many countries have taken measures to control the free circulation of these products. Though, clandestine street manufacturers change the chemical structures to evade law enforcement [2 ]. Consequently, new SC are constantly appearing on the market, making it proliferation and use difficult to control [3 ]. The major consequences of contemporary NPS use are an increasing number of hospitalizations and fatalities. Previously we put forward that JWH-018, the first SC found on the streets, is not toxic per se to human neuroblastoma cells [4 ]. In this study we propose that the modifications that SC have been undergoing to avoid the law are potentiating the toxicity and hazard of emerging SC. Materials and methods: JWH-018 and EG-018 acquired had a purity degree of 99%. The human neuroblastoma SH-SY5Y cells were grown in DMEM supplemented with 10% (v/v) fetal bovine serum and 1% (v/v) Pen/Strep-Glutamine and cultured in humidified 5% CO2 at 37 °C. The media were changed every 3–4 days and the cultures were removed for cell assays when at 80% confluence. For the viability assays the cells were seeded at a density of 5 × 10 4 cells per well in 96-well plates, allowed to attach. Then the cells were exposed, for 24 hours, to several concentrations of each SC and its viability was assessed through MTT assays. Results: MTT results for SH-SY5Y cells in the presence of JWH-018 and EG-018 (Figure 1 ) show that cell viability does not decrease in the presence of JWH-018 at the range of concentrations used. However, when the same cell line was exposed to EG-018 there is a decrease in cell viability with the increase in the concentration of this substance. Discussion and conclusions: The results from the present study points EG-018, a new SC appearing on the market, as more toxic to the neuroblastoma cells than JWH-018, the first SC found on the street in 2008. These results suggest that emerging modified SC, to avoid the law, may become more toxic and dangerous. Given the emergence of this situation, it is time to rethink current legislation to prevent rise on public health issues derived from consumption of molecules of unknown toxicological profile.